Electrophysiological differences between upper and lower limb movements in the human subthalamic nucleus - Tinkhauser, G; Shah, A; Fischer, P; Peterman, K; Debove, I; Nygyuen, K; Nowacki, A; Torrecillos, F; Khawaldeh, S; Tan, H; Pogosyan, A; Schuepbach, M; et al. (Elsevier, 2019)
Objective: Functional processes in the brain are segregated in both the spatial and spectral domain. Motivated by findings reported at the cortical level in healthy participants we test the hypothesis in the basal ganglia of Parkinson’s disease patients that lower frequency beta band activity relates to motor circuits associated with the upper limb and higher beta frequencies with lower limb movements. Methods: We recorded local field potentials (LFPs) from the subthalamic nucleus using segmented “directional” DBS leads, during which patients performed repetitive upper and lower limb movements. Movement-related spectral changes in the beta and gamma frequency-ranges and their spatial distributions were compared between limbs. Results: We found that the beta desynchronization during leg movements is characterised by a strikingly greater involvement of higher beta frequencies (24–31 Hz), regardless of whether this was contralateral or ipsilateral to the limb moved. The spatial distribution of limb-specific movement-related changes was evident at higher gamma frequencies. Conclusion: Limb processing in the basal ganglia is differentially organised in the spectral and spatial domain and can be captured by directional DBS leads. Significance: These findings may help to refine the use of the subthalamic LFPs as a control signal for adaptive DBS and neuroprosthetic devices.